A STUDY OF THE ADSORPTION OF DYES FROM THEIR AQUEOUS SOLUTIONS BY MORUPULE COAL 1 - Nadiye-Tabbiruka, Misael Silas; Sejie, Foertunate Phenyo; Salamula, Estella Judith (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
The adsorption of methyl orange (MO) from its solution by steam activated coal from Morupule colliery was investigated spectrophotometrically using the batch technique, through kinetics and thermodynamicsâ€™ study, and found to be reversible at all temperatures used. This was to check whether the coal could be used to purify dye-polluted water from dying and printing textile industry. The effects of varying methyl orange concentration, solution pH and temperature were investigated. The adsorption rate and the adsorption capacity increased with increasing initial concentration, with decreasing solution pH and with increasing temperature. The adsorption capacity was generally low probably due to the low coal surface area (10 m2g-1). The increase in rate and capacity with increasing temperature is believed to be increased surface area due to the swelling of coal which accompanies its heating.Â The adsorption kinetics fitted the Lagergren pseudo second order model best indicating overall third order or dual simultaneous pseudo first order processes. Results from the thermodynamic study fitted Â Freundlich model best indicating heterogeneity of the surface of the coal sample.Â